Meneladani Akhlak Rasulullah Saw. dalam Perspektif Hadis: Studi Takhrij dan Syarah Hadis - Farhan Bahrul Ulum (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about imitating the morals of the Prophet Muhammad. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the morals of the Prophet Muhammad. in the history of Tirmidhi No. 1930. The results and discussion of this study indicate that the status of hasan li ghairihi hadiths that meet the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Tirmidhi No. 1930 is relevant to be used as a motivation to always imitate the morals of the Prophet Muhammad. in doing good.